2016
DOI: 10.1074/jbc.m115.699470
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin-B Modulates Collagen Cross-linking by Differentially Affecting Lysine Hydroxylation in the Helical and Telopeptidyl Domains of Tendon Type I Collagen

Abstract: Covalent intermolecular cross-linking provides collagen fibrils with stability. The cross-linking chemistry is tissue-specific and determined primarily by the state of lysine hydroxylation at specific sites. A recent study on cyclophilin B (CypB) null mice, a model of recessive osteogenesis imperfecta, demonstrated that lysine hydroxylation at the helical cross-linking site of bone type I collagen was diminished in these animals (Cabral, W. A., Perdivara, I., Weis, M., Terajima, M., Blissett, A. R., Chang, W.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(113 citation statements)
references
References 50 publications
13
100
0
Order By: Relevance
“…In contrast, it has been reported that the PPIase activity of FKBP65 is not involved in the modulation of the coacervation and in vitro self-assembly of human tropoelastin3940, indicating that FKBP65 regulates different biologic processes through different mechanisms. Recently, we reported that the PPIase cyclophilin B interacts with all LH1-3 and FKBP65, and that loss of cyclophilin B in mice leads to enhanced LH2 activity generating HLCCs in tendon type 1 collagen41. These together with the current findings strongly indicate an intricate interplay of these ER-resident PPIases with specific LH isoforms, thus, tightly controlling this important post-translational modification42.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In contrast, it has been reported that the PPIase activity of FKBP65 is not involved in the modulation of the coacervation and in vitro self-assembly of human tropoelastin3940, indicating that FKBP65 regulates different biologic processes through different mechanisms. Recently, we reported that the PPIase cyclophilin B interacts with all LH1-3 and FKBP65, and that loss of cyclophilin B in mice leads to enhanced LH2 activity generating HLCCs in tendon type 1 collagen41. These together with the current findings strongly indicate an intricate interplay of these ER-resident PPIases with specific LH isoforms, thus, tightly controlling this important post-translational modification42.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, the specific and dynamic cross-linking pattern in bone/dentin type 1 collagen is important to regulate the process of collagen mineralization45464748. However, the tissue-specific cross-linking pattern cannot be explained solely by the respective LH gene expression41. Likely, these multifaceted post-translational control mechanisms of LH function are, in part, an important contributor to the cell- and tissue-specific collagen cross-linking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of CypB for collagen post-translational modification became clear from the effects of PPIB mutations that cause severe osteogenesis imperfecta. They result in loss of prolyl-hydroxylation at Pro-986 (27) and, in CypB knock-out mice, defective lysine hydroxylation in bone (28) and tendon (29) collagens. Furthermore, we know that FKBP65, another peptidyl prolyl isomerase and ER chaperone, can regulate the activity of LH2 the predicted telopeptide lysine hydroxylase (12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…CypB is an ER-resident peptidyl-prolyl cis-trans isomerase and was the first molecule shown to be associated with LH1 [46]. The absence of CypB or disruption of the interaction with LH1 results in the reduction of lysyl hydroxylation in tendon and skin [31, 32], while the amount of lysyl hydroxylation is increased in bone [47]. Additionally, there is a site-specific effect to the level of lysyl hydroxylation in tendon, skin and bone.…”
Section: Discussionmentioning
confidence: 99%